P1-S2.32 Do as I think, not as I do: the discordance between perception of risk for STBBIs and sexual risk behaviours among Canadian street-involved youth. (10th July 2011) - Fang, L; Klar, S A; Friedman, D; Gratrix, J; Rossi, M; Tawse, C; Taylor, D; Wright, J; Wylie, J; Wong, T; Jayaraman, G C; ,
Abstract : Background: Canadian street-involved youth are perceived to be at greater risk for sexually transmitted and bloodborne infections (STBBI) and may be more vulnerable to these infections because of their age, socioeconomic status, life course factors, and engagement in high risk behaviours. However, perception of their own risks and the behaviours that influence this perception are less understood and will be described using the Enhanced Surveillance of Canadian Street Youth (E-SYS) data. Methods: E-SYS is a repeated cross-sectional surveillance study of street-involved youth (15–24 years). Preliminary data from Cycle 6 (2009-present) (n=705) were used to determine how these youth perceive their risk for STBBI and factors that contribute to perception. Participants completed an interviewer-administered questionnaire and provided sera and urine samples for STBBI testing. Chi-square tests and unadjusted ORs were performed to assess these relationships (α=0.05, 2-sided). Results: Among interviewed street-involved youth, 65.8% reported that they felt they were at no or low risk of being infected with an STBBI. Age and gender did not influence perception of risk for STBBI. Factors that were significantly associated with medium or high perception of risk for STBBI included being bisexual (OR 1.6, 95% CI 1.1 to 2.3), having sex while under the influence of drugs or alcohol (OR 2.5, 95% CI 1.5 to 4.1), and not being aware of where to access health services (OR 1.7, 95% CI 1.1 to 2.6). Although engaging in anal sex affected their perception of risk for STBBI (p<0.05), having vaginal sex did not (p=0.75). Those who did not use a contraceptive barrier (eg, condom) when they last had vaginal sex felt they were at greater risk for an STBBI (OR 1.7, 95% CI 1.2 to 2.3), but barrier use during anal sex did not affect their perception of risk (p=0.3). Conclusions: Although many street-involved youth acknowledge that certain behaviours may put them at greater risk for STBBI, they continue to engage in these behaviours. These youth may not be fully knowledgeable about the extent to which certain risks enhance STBBI transmission or options for altering behaviours may be limited. Of concern is our finding that some youth, who perceive themselves as being at medium or high risk for an STBBI, may not know where to access services for STBBI counselling, testing, and treatment. Concerted efforts continue to be needed to engage this population and to translate knowledge into action.